A Pilot Study on Psychological Safety in Diagnostic Medical Sonography Education. - Renfro, Mary Grace; Aaron, Laura; Steele-Moses, Susan (Radiologic Science & Education, 2023)
New research has emerged discussing the importance of psychological safety, which is lacking in radiologic sciences education. This provided an opportunity for a pilot study with students and graduates of the diagnostic medical sonography (DMS) program at a private health sciences university. Twenty-nine participants completed the survey, with a mean score of 100.52 out of 140. Despite the small sample, specific educationally significant trends were discovered. Psychological safety improved with student progression in the program and was slightly higher in the classroom and laboratory than in clinical environments. These results could lead to improved psychological safety in other radiologic sciences programs.